Understanding sectoral differences in downward real wage rigidity: workforce composition, institutions, technology and competition - Philip Du Caju; Catherine Fuss; Ladislav Wintr (National Bank of Belgium, 2009)
This paper examines whether differences in wage rigidity across sectors can be explained by differences in workforce composition, competition, technology and wage-bargaining institutions. We adopt the measure of downward real wage rigidity (DRWR) developed by Dickens and Goette (2006) and rely on a large administrative matched employer-employee dataset for Belgium over the period 1990-2002. Firstly, our results indicate that DRWR is significantly higher for white-collar workers and lower for older workers and for workers with higher earnings and bonuses. Secondly, beyond labour force composition effects, sectoral differences in DRWR are related to competition, firm size, technology and wage-bargaining institutions. We find that wages are more rigid in more competitive sectors, in labour-intensive sectors, and in sectors with predominant centralised wagesetting at the sector level as opposed to firm-level wage agreements.
Keywords: J31; 330; wage rigidity; matched employer-employee data; wage-bargaining institutions; Lohnrigidität; Branche; Belgien